SnO2 electron transport layer, preparation method thereof and perovskite solar cell

The tin source film layer is formed on the conductive glass by thermal evaporation, and combined with the coating of the SnO2 precursor solution and air annealing, the problems of unstable quality and insufficient density of the electron transport layer in the prior art are solved, and the performance improvement of the perovskite solar cell is achieved.

CN119730663APending Publication Date: 2025-03-28TAN KAH KEE INNOVATION LAB
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411822637.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art has problems such as unstable mass, insufficient density and difficulty in controlling high power conversion efficiency when preparing electron transport layers of high-performance perovskite solar cells.

Method used

A tin source film layer is formed on the conductive glass by thermal evaporation method, and then the SnO2 precursor solution is coated and air annealed to achieve high-quality preparation of the SnO2 electron transport layer.

Benefits of technology

This method simplifies the process flow, improves the density and crystallinity of the electron transport layer, and significantly improves the photoelectric conversion efficiency and stability of perovskite solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730663A_ABST
    Figure CN119730663A_ABST
Patent Text Reader

Abstract

The invention provides a SnO2 electron transport layer and a preparation method thereof, and a perovskite solar cell. The preparation method of the SnO2 electron transport layer comprises the following steps: (1) thermally evaporating a tin source to conductive glass to form a film layer; the tin source is selected from SnO, Sn or SnCl2; and (2) coating a SnO2 precursor solution on the film layer, then carrying out air annealing, and forming a SnO2 electron transport layer on the conductive glass. The thin film layer is formed by thermal evaporation of the tin source, then the SnO2 precursor solution is coated, the film layer formed by the tin source and the precursor are cooperated for tin dioxide in-situ growth only through one-time annealing process, the tin dioxide thin film with good compactness and high crystallization degree is prepared, and uniform covering on the substrate is achieved. The method has the advantages of large scale, high repeatability and high yield, and the uniform and compact electron transport layer with strong electron transport capability is finally obtained. According to the perovskite solar cell constructed on the basis of the electron transport layer, the photoelectric conversion efficiency, the stability and other properties are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite solar cells, and in particular to a SnO 2 Electron transport layer and preparation method thereof, and perovskite solar cell. Background Art

[0002] In the photovoltaic field, the electron transport layer refers to the key layer in the solar cell used to transport photogenerated carriers (i.e., photogenerated electrons and holes). Photovoltaic cells are devices that convert solar energy into electrical energy, in which the electron transport layer plays an important role. Especially in solar cells with an upright structure, the electron transport layer, as the first film layer to come into contact with sunlight, plays a particularly critical role as a substrate. This requires that the electron transport layer not only has good electron transport and hole blocking capabilities, but also serves as a substrate for perovskite film formation, has dense, stable, and flat characteristics, and exhibits good material stability and interface stability.

[0003] At present, the commonly used electron transport layers are mainly concentrated in inorganic electron transport layers, such as titanium dioxide, zinc oxide and tin dioxide (SnO 2 ) etc. With the deepening of research and the development of technology, SnO 2 Due to its high electron mobility (100-200cm 2 ·V / s) and good stability (compared with the poor UV stability of titanium dioxide and the easy adsorption of hydroxyl groups by zinc oxide, which leads to reduced stability of perovskite), as well as the ability to be prepared at low temperature, show broad prospects for industrial expansion.

[0004] Traditional SnO 2 The preparation of electron transport layers, whether it is chemical bath deposition (CBD), coating with commercial colloidal nanoparticles, or direct precursor coating and annealing, has obvious shortcomings. The CBD method is time-consuming and difficult to scale up, which limits its large-scale application; although commercial colloids are easy to use, they lack precise control over key properties such as high power conversion efficiency (PCE), and the film quality is unstable, the uniformity and density are insufficient, and the commercial source is also unstable; and the method of directly coating the precursor and annealing can also quickly form a film, but the quality of the film is difficult to guarantee, and the coverage uniformity and density on substrates such as conductive glass are poor. These shortcomings have jointly hindered the application of these traditional preparation methods in high-performance batteries.

[0005] The patent "CN115915871A / A composite electron transport layer and its preparation method and application" prepares a metal oxide electron transport layer by thermally evaporating a metal element in an oxygen-containing atmosphere, and evaporates organic materials to form a composite organic-inorganic electron layer, which is applied to inverted perovskite solar cells. This method avoids the damage to the battery caused by magnetron sputtering, but does not consider the application in the upright structure, and uses organic electronic layer materials to improve the transmission capacity, without regulating the crystallization behavior of tin dioxide. In addition, the method in this patent evaporates under oxygen conditions, which poses a risk of potential damage to the battery.

[0006] The patent "CN109553126A / A method for preparing tin dioxide crystals by thermal evaporation" uses SnO as the source material to prepare tin dioxide crystals in an argon atmosphere, but this method uses the reaction 2SnO=SnO 2 + Sn to prepare tin dioxide will inevitably produce Sn. If not further processed, the doped metal Sn will affect the performance of the semiconductor electron transport layer. The method in this patent completes the conversion at high temperature in an inert gas, but no post-annealing operation is performed, resulting in residual Sn element, which is harmful to semiconductor devices.

[0007] Preparation of SnO by magnetron sputtering and thermal evaporation 2 "Nanomaterials and Structural Characterization" (Zhang Xiaosen, academic paper) uses tin powder as raw material and explores the effects of different temperatures and different doping elements on growth. The thermal evaporation method is limited to a tube furnace, the sample size is small, and the direct high-temperature preparation method cannot be applied to the perovskite field, because the tolerance temperature of perovskite cells is usually not higher than 150°C. In short, this method limits the sample size, and the high-temperature growth environment is not suitable for the perovskite battery field.

[0008] Therefore, how to prepare a perovskite photovoltaic electron transport layer that is uniform, dense, highly crystallized, and has excellent electron transport capability to improve the overall performance of the device is a technical problem that urgently needs to be solved in the current photovoltaic field. Summary of the invention

[0009] In view of the above problems, the present invention provides a SnO 2 Electron transport layer and preparation method thereof, and perovskite solar cell.

[0010] In one aspect, the present invention provides a SnO 2 The method for preparing an electron transport layer comprises the following steps:

[0011] (1) thermally evaporating a tin source onto the conductive glass to form a film layer; wherein the tin source is selected from SnO, Sn or SnCl 2 ;

[0012] (2) Coating SnO on the film2 Precursor solution, followed by air annealing, to form SnO on conductive glass 2 Electron transport layer.

[0013] On the other hand, the present invention also provides a SnO 2 The electron transport layer is prepared by the above-mentioned preparation method.

[0014] In another aspect, the present invention further provides a perovskite solar cell, wherein the electron transport layer on the conductive glass is the aforementioned SnO 2 Electron transport layer.

[0015] Beneficial effects:

[0016] (1) The preparation method of the present invention simplifies the process flow of the tin dioxide electron transport layer and improves its quality. A thin film is first formed by thermal evaporation of a tin source, and then coated with SnO 2 The precursor solution only needs one air annealing. In this process, the thin film formed by the tin source acts as an auxiliary layer, which can effectively promote the in-situ growth of tin dioxide in the precursor solution. At the same time, the tin source auxiliary layer is also converted into tin dioxide in the air, thereby preparing a tin dioxide film with excellent density and high crystallinity. This preparation method not only simplifies the process flow, but also enables the final electron transport layer to achieve conformal growth on a substrate such as transparent conductive glass, and has the characteristics of uniform density and strong electron transport capability.

[0017] (2) Based on the SnO 2 The key performance indicators of perovskite solar cells, such as the electron transport layer, photoelectric conversion efficiency and stability, have been significantly improved. This is due to the high quality of the electron transport layer, which enables solar cells to more effectively capture and transmit photogenerated electrons, thereby improving the overall performance and reliability of the cell.

[0018] (3) The preparation process of the present invention is characterized by scalability, high repeatability and high yield rate. Since the process steps are concise and clear, and the cost of required materials and equipment is relatively low, the process is very suitable for large-scale production. At the same time, by precisely controlling various parameters in the preparation process, such as the selection of tin source, thermal evaporation temperature, coating speed and annealing conditions, it can be ensured that a tin dioxide electron transport layer with stable performance and high quality can be obtained each time. This highly repeatable preparation process not only improves production efficiency, but also helps to reduce production costs and enhance the market competitiveness of products. In addition, a high yield rate means that in mass production, the generation of defective and waste products can be reduced, further reducing losses and improving overall economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1A schematic diagram of the structure of an upright perovskite solar cell prepared according to an embodiment of the present invention;

[0020] Figure 2 This is a graph showing IV efficiency tests of battery devices prepared in Example 1 and Comparative Examples 1 to 4 of the present invention;

[0021] Figure 3 This is a graph showing the efficiency change in the light stability test of the battery devices prepared in Example 1 and Comparative Examples 2 to 4 of the present invention;

[0022] Figure 4 The scanning electron microscope photographs of the electron transport layer prepared by step (A) in Example 1, Comparative Example 2 and Comparative Example 3 of the present invention are shown;

[0023] Figure 5 The cyclic voltammetry (CV) test results of the electron transport layer prepared by step (A) in Example 1 and Comparative Example 3 of the present invention;

[0024] Figure 6 The X-ray diffraction (XRD) test results of the powder of the electron transport layer prepared in step (A) of Example 1, Comparative Example 2 and Comparative Example 3 of the present invention and the stannous oxide powder are shown. DETAILED DESCRIPTION

[0025] The present application is further described in detail below through the accompanying drawings and embodiments. Through these descriptions, the characteristics and advantages of the present application will become clearer and more specific.

[0026] The word "exemplary" is used exclusively herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments. Although various aspects of the embodiments are shown in the drawings, the drawings are not necessarily drawn to scale unless otherwise noted.

[0027] In addition, the technical features involved in different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.

[0028] In one aspect, the present invention provides a SnO 2 The method for preparing an electron transport layer comprises the following steps:

[0029] (1) thermally evaporating a tin source onto the conductive glass to form a film layer; wherein the tin source is selected from SnO, Sn or SnCl 2 ;

[0030] (2) Coating SnO on the film 2 Precursor solution, followed by air annealing, to form SnO on conductive glass 2 Electron transport layer.

[0031] It should be noted that the preparation method of the present invention uses evaporable tin materials SnO, Sn or SnCl 2 As a tin source, a film layer is formed on the upper surface of the conductive glass by thermal evaporation. For example, when SnO is used as a tin source, a SnO film layer is formed by thermal evaporation. After the film layer is formed by thermal evaporation, no annealing is performed; then SnO is coated 2 The precursor solution is then air annealed. The coating can be done by scraping, slit coating, screen printing, spraying, etc. In this way, during the annealing process, the SnO film layer and SnO 2 The precursors are converted into SnO through annealing process. 2 , quickly and easily achieve high quality SnO 2 Preparation of electron transport layer solves the problem of SnO 2 The problem of difficult sublimation and evaporation is solved by combining evaporation with coating and one-step air annealing to realize SnO 2 Preparation of electron transport layer.

[0032] The present invention first uses a specific tin source through a specific method-thermal evaporation to form a film layer on the conductive glass, and the film layer is not annealed separately, and then a specific method-coating method is used to coat the surface of the film layer with SnO 2 The precursor solution is finally annealed in air, and the film formed by the tin source assists SnO 2 The precursor grows in situ, promoting the conformal growth of the electron transport layer, improving the energy level distribution of the electron transport layer, adjusting the oxygen vacancy arrangement, and adjusting the oxygen vacancy concentration and energy level gradient distribution of the electron transport layer to obtain uniform, dense, high-purity, high-crystalline SnO with strong electron transport ability. 2 Electron transport layer, based on such SnO 2 Perovskite solar cells constructed with electron transport layers have excellent performance, with significantly improved properties such as photoelectric conversion efficiency and stability.

[0033] When the tin source is Sn or SnCl 2 When the thermal evaporation process is carried out on the conductive glass, the film layers formed are Sn film layer, SnCl 2 After years of research and development, the inventor of this application unexpectedly discovered that when SnO is used as the tin source, the SnO film layer formed by thermal evaporation can be coated with SnO 2 When the electron transport layer is prepared by a precursor solution and a single annealing step, the SnO film layer can better assist the SnO 2 Precursor in situ growth, SnO and SnO 2 The precursor can better conformally grow to improve the density of the electron transport layer and the film quality of the electron transport layer. 2The electron transport layer is more uniform, dense, and continuous, and has higher electron mobility and better electron transport capacity. The constructed perovskite solar cell can simultaneously achieve excellent photoelectric conversion efficiency and stability and other properties.

[0034] In one embodiment of the above preparation method of the present invention, in step (1), thermally evaporating the tin source onto the conductive glass to form a film layer comprises the following steps:

[0035] (S1) placing the conductive glass on a deposition substrate, 40 to 50 cm away from an evaporation source;

[0036] (S2) placing the tin source as the source material in the evaporation boat area, and evacuating the environment to 8×10 -5 Pa, the tin source is evaporated onto the conductive glass at a rate of 0.1-1 A / s to form a film layer.

[0037] Specifically, the rate at which the tin source evaporates onto the conductive glass can be 0.2 A / s, 0.3 A / s, 0.4 A / s, 0.5 A / s, 0.6 A / s, 0.7 A / s, 0.8 A / s, 0.9 A / s, etc.

[0038] Compared with physical methods such as magnetron sputtering and single atom deposition, the present invention uses thermal evaporation (thermal evaporation) to obtain a film layer with good crystal quality and good uniformity at a faster speed, and is convenient for expansion and expansion of production. The present invention uses thermal evaporation under vacuum conditions to obtain a uniform and dense film layer, reduce leakage, and does not limit annealing conditions due to perovskite. In particular, steps (S1) and (S2) are performed as above, and SnO with better performance can be prepared through subsequent steps. 2 Electron transport layer.

[0039] In another embodiment of the above preparation method of the present invention, the thickness of the film layer obtained in step (1) is 1 to 20 nm, preferably 1 to 15 nm.

[0040] Specifically, the thickness of the film layer can be 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, etc. Step (1) thermally evaporates a tin source to form a film layer on the conductive glass. The mass of the evaporated tin source can be 1g. At this time, a film layer with a thickness of about 5nm and a width (size) of about 30cm×40cm can be formed on the conductive glass. By controlling the thickness of the above film layer as above, the film layer can better assist SnO 2 The in-situ growth of the precursor promotes the conformal growth of the electron transport layer, which is beneficial to obtain SnO with better density, continuity and crystallization. 2 Electron transport layer.

[0041] In another embodiment of the above preparation method of the present invention, the SnO obtained in step (2) 2 The thickness of the electron transport layer is 2 to 50 nm, preferably 20 to 40 nm.

[0042] Specifically, the above SnO 2 The thickness of the electron transport layer can be 10 nm, 15 nm, 25 nm, 26 nm, 27 nm, 28 nm, 29 nm, 30 nm, 31 nm, 32 nm, 33 nm, 34 nm, 35 nm, 36 nm, 37 nm, 38 nm, 39 nm, etc. 2 The thickness of the electron transport layer refers to the thickness of the film layer and the coating SnO 2 SnO obtained by annealing the precursor 2 The total thickness of the electron transport layer. While controlling the film thickness as above, further control the SnO 2 The thickness of the electron transport layer can further increase the SnO 2 The compactness and charge transport capacity of the electron transport layer.

[0043] In one embodiment of the preparation method of the present invention, the annealing in step (2) is carried out in an atmospheric environment at 150-500° C. for 0.25-12 h, preferably at 150-400° C. for 0.25-4 h, and more preferably firstly heating from 80-120° C. to 180-220° C. over 15-45 min, and then annealing at this temperature for 15-45 min.

[0044] It should be noted that in a further preferred annealing implementation, the temperature is raised from 80 to 120°C to 180 to 220°C over 15 to 45 minutes. This heating process can be a constant rate heating process. Specifically, the temperature can be raised from 80°C, 90°C, 100°C, 110°C, 120°C to 180°C, 190°C, 200°C, 210°C, 220°C over 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, etc. In addition, after the annealing in step (2) is completed, it can also be cooled naturally to finally obtain SnO on the conductive glass. 2 Electron transport layer. By controlling the conditions of the annealing process as above, especially as above, the film layer can better assist SnO 2 Precursor growth, ensuring film and SnO 2 The precursor is completely converted into SnO 2 , which can better construct the energy level gradient distribution and oxygen vacancy distribution of the electron transport layer to further improve the SnO 2The density and charge transport capacity of the electron transport layer can be improved to further improve the photoelectric conversion efficiency and stability of the final battery device.

[0045] In one embodiment of the above preparation method of the present invention, the SnO 2 The precursor solution is selected from tin tetrachloride, stannous chloride, sodium stannate, Sn(N(CH 3 ) 2 ) 4 A solution of one or more components.

[0046] It should be noted that SnO 2 The precursor solution is preferably a tin tetrachloride solution. Tin tetrachloride as a precursor can better grow in situ with the assistance of the film layer formed by the tin source, thereby obtaining a SnO with better compactness and charge transfer ability. 2 Electron transport layer. In particular, SnO 2 The precursor solution is preferably a 5-20 wt% tin tetrachloride solution, and the coating speed in step (2) is preferably 1000-5000 rpm. 2 The concentration of the precursor solution and the coating speed are comprehensively controlled to obtain the SnO 2 The precursor particles in the precursor coating have a specific concentration, distribution, etc., and then when the subsequent annealing is carried out together with the film layer obtained by thermal evaporation, the tin source in the film layer and the SnO in the coating layer 2 The precursor particles can better coexist in situ to obtain a denser, continuous and uniform electron transport layer, and the charge transfer capacity of the electron transport layer is also correspondingly better.

[0047] On the other hand, the present invention also provides a SnO 2 The electron transport layer is prepared by adopting the above preparation method.

[0048] It should be noted that the SnO 2 The electron transport layer is a thermally evaporated tin source film and SnO 2 The SnO 2 The electron transport layer is uniform and dense, high-purity and high-crystalline, and has excellent electron transport capability when used as a substrate for the electron transport layer.

[0049] In another aspect, the present invention further provides a perovskite solar cell, wherein the electron transport layer on the conductive glass is the above-mentioned SnO 2 Electron transport layer.

[0050] The electron transport layer in the perovskite solar cell of the present invention is the above-mentioned SnO 2 Electron transport layer, because SnO 2The electron transport layer is dense and has excellent charge transport capabilities, so the performance of perovskite solar cells is excellent.

[0051] In one embodiment of the above-mentioned perovskite solar cell of the present invention, it also includes a perovskite layer, a hole transport layer and a counter electrode layer located on the electron transport layer.

[0052] It should be noted that the SnO 2 The electron transport layer is more suitable for the normal perovskite solar cell, that is, the nip structure perovskite solar cell, which is composed of a conductive glass electrode layer, an electron transport layer, a perovskite layer, a hole transport layer and a counter electrode layer from bottom to top. The electron transport layer is the above-mentioned SnO 2 Electron transport layer. In the upright device, SnO 2 The electron transport layer can exert better electron transport capability, and the device has better photoelectric conversion efficiency and stability.

[0053] In another embodiment of the above-mentioned perovskite solar cell of the present invention, the thickness of the perovskite layer is 300 to 700 nm;

[0054] The perovskite material in the perovskite layer has ABX 3 A semiconductor compound with a structure; wherein A is one or more monovalent organic cations selected from amine, amidine, guanidine and cesium; B is one or more metal ions selected from lead, tin, rubidium, silver, bismuth, silicon and magnesium, and the molar percentage of lead ions in B is not less than 50%; X is one or more selected from iodide, chloride, bromide, thiocyanate and acetate;

[0055] The thickness of the hole transport layer is 60 to 120 nm;

[0056] The organic hole material in the hole transport layer is one or more selected from Spiro-OMeTAD, poly-TPD, copper phthalocyanine, nickel phthalocyanine, high molecular weight poly(triarylamine) and poly(3-hexylthiophene);

[0057] The thickness of the counter electrode layer is 60 to 120 nm;

[0058] The electrode material in the counter electrode layer is one or more selected from gold, silver, copper, nickel, tin, carbon and ITO.

[0059] In addition, the present invention can also provide a method for preparing the above-mentioned perovskite solar cell, comprising the following steps:

[0060] (A) SnO was prepared on conductive glass as above 2 Electron transport layer;

[0061] (B) In SnO2 preparing a perovskite layer on the electron transport layer;

[0062] The perovskite material solution of 1-2 mol / L can be heated at a speed of 3000-7000 rpm in a SnO 2 The electron transport layer is coated, an anti-solvent such as chlorobenzene is added dropwise at 10 to 20 seconds, and then annealed at 100 to 150° C. for 30 to 90 minutes, and cooled naturally to obtain a perovskite layer;

[0063] (C) preparing a hole transport layer on the perovskite layer;

[0064] Wherein, the dispersion of the organic hole material can be coated on the perovskite layer at a speed of 3000 to 7000 rpm, and then dried naturally to obtain a hole transport layer;

[0065] (D) preparing a counter electrode layer on the hole transport layer;

[0066] wherein, an electrode material is evaporated on the hole transport layer to obtain a counter electrode layer;

[0067] Finally, a perovskite solar cell is obtained.

[0068] The present invention is further described in detail by way of examples below, but the present invention is not limited thereto. In the following examples, unless otherwise specified, the experimental instruments and raw materials involved are all commercially available products.

[0069] In the following examples and comparative examples, the metal boat (evaporation boat) is heated by controlling the power, and the film thickness meter is used to achieve material evaporation and thickness control. In the following examples and comparative examples, the temperature is increased from 100°C to 200°C for 30 minutes, and the heating process can be a constant speed heating process.

[0070] Example 1

[0071] according to Figure 1 The steps for preparing the inverted perovskite solar cell are as follows:

[0072] Step (A) comprises the following steps (A-1) to (A-4):

[0073] Step (A-1): Place a clean transparent conductive glass 1 (FTO glass) on a deposition substrate, 40 to 50 cm from the evaporation source;

[0074] Step (A-2): placing stannous oxide as a source material in the evaporation boat area;

[0075] Step (A-3): Use a pump set to evacuate the environment to a vacuum of 8 × 10 -5Below Pa, the evaporation rate is controlled to 0.2A / s, and the thickness of the prepared film is controlled to 5nm;

[0076] Step (A-4): 10 wt% tin tetrachloride solution is coated on the film layer on the above-treated transparent conductive glass by a solution method to prepare SnO 2 The coating speed is 3000rpm. After coating, the temperature is raised from 100℃ to 200℃ for 30min. After annealing at 200℃ for 30min, the film is cooled naturally. A total film thickness of 30nm of SnO is obtained on the transparent conductive glass 1. 2 Electron transport layer 2;

[0077] Step (B), preparation of perovskite layer 3: coating FA with a concentration of 1.4 mol / L on the electron transport layer 2 of step (A) 0.95 Cs 0.05 PbI 3 solution, the coating condition is 5000rpm, the coating time is 30s, chlorobenzene is added as anti-solvent at 15s, annealing is performed at 110°C for 60min, and natural cooling is performed to obtain a perovskite layer 3 with a thickness of 660-700nm;

[0078] Step (C), preparing a chlorobenzene dispersion of Spiro-OMeTAD: dissolving 520 mg of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) in 1 mL of acetonitrile, stirring for 3 min, then dissolving 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene, adding 28.8 μL of 4-tert-butylpyridine (TBP) and 17.5 μL of Li-TFSI acetonitrile solution to prepare a chlorobenzene dispersion of Spiro-OMeTAD; coating the perovskite layer 3 by a solution method at a coating speed of 4000 rpm, and drying naturally to obtain a hole transport layer 4 with a film thickness of 80 nm;

[0079] Step (D), preparing the counter electrode layer 5: evaporating gold on the hole transport layer 4 to obtain the counter electrode layer 5 with a film thickness of 110 nm.

[0080] Thus, a normal perovskite solar cell was obtained, which was recorded as C-1.

[0081] Example 2 (Variation of film thickness in step (A-3) and step (A-4))

[0082] according to Figure 1 The steps for preparing the inverted perovskite solar cell are as follows:

[0083] Step (A) comprises the following steps (A-1) to (A-4):

[0084] Step (A-1): Place a clean transparent conductive glass 1 on a deposition substrate, 40 to 50 cm from the evaporation source;

[0085] Step (A-2): placing stannous oxide as a source material in the evaporation boat area;

[0086] Step (A-3): Use a pump set to evacuate the environment to a vacuum of 8 × 10 -5 Below Pa, the evaporation rate is controlled to 0.2A / s, and the thickness of the prepared film is controlled to 1nm;

[0087] Step (A-4): 10 wt% tin tetrachloride solution is coated on the film layer on the above-treated transparent conductive glass by a solution method to prepare SnO 2 The coating speed was 3000 rpm. After coating, the temperature was raised from 100°C to 200°C for 30 min. After annealing at 200°C for 30 min, the film was cooled naturally. A total film thickness of 26 nm of SnO was obtained on the transparent conductive glass 1. 2 Electron transport layer 2;

[0088] Step (B), preparation of perovskite layer 3: coating FA with a concentration of 1.4 mol / L on the electron transport layer 2 of step (A) 0.95 Cs 0.05 PbI 3 The coating condition is 5000 rpm, the coating time is 30 s, chlorobenzene is added as an anti-solvent at 15 s, annealing is performed at 110 ° C for 60 min, and natural cooling is performed to obtain a perovskite layer 3 with a thickness of 650-690 nm;

[0089] Step (C), preparing a chlorobenzene dispersion of Spiro-OMeTAD: dissolving 520 mg of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) in 1 mL of acetonitrile, stirring for 3 min, then dissolving 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene, adding 28.8 μL of 4-tert-butylpyridine (TBP) and 17.5 μL of Li-TFSI acetonitrile solution to prepare a chlorobenzene dispersion of Spiro-OMeTAD; coating the perovskite layer 3 by a solution method at a coating speed of 4000 rpm, and drying naturally to obtain a hole transport layer 4 with a film thickness of 80 nm;

[0090] Step (D), preparing the counter electrode layer 5: evaporating gold on the hole transport layer 4 to obtain the counter electrode layer 5 with a film thickness of 110 nm.

[0091] Thus, a normal perovskite solar cell was obtained, which was recorded as C-2.

[0092] Example 3 (Variation of film thickness in step (A-3) and step (A-4))

[0093] according to Figure 1 The steps for preparing the inverted perovskite solar cell are as follows:

[0094] Step (A) comprises the following steps (A-1) to (A-4):

[0095] Step (A-1): Place a clean transparent conductive glass 1 on a deposition substrate, 40 to 50 cm from the evaporation source;

[0096] Step (A-2): placing stannous oxide as a source material in the evaporation boat area;

[0097] Step (A-3): Use a pump set to evacuate the environment to a vacuum of 8 × 10 -5 Below Pa, the evaporation rate is controlled to 0.2A / s, and the thickness of the prepared film is controlled to 10nm;

[0098] Step (A-4): 10 wt% tin tetrachloride solution is coated on the film layer on the above-treated transparent conductive glass by a solution method to prepare SnO 2 The coating speed was 3000 rpm. After coating, the temperature was raised from 100°C to 200°C for 30 min. After annealing at 200°C for 30 min, the film was cooled naturally. A total film thickness of 31 nm of SnO was obtained on the transparent conductive glass 1. 2 Electron transport layer 2;

[0099] Step (B), preparation of perovskite layer 3: coating FA with a concentration of 1.4 mol / L on the electron transport layer 2 of step (A) 0.95 Cs 0.05 PbI 3 solution, the coating condition is 5000rpm, the coating time is 30s, chlorobenzene is added as anti-solvent at 15s, annealing is performed at 110℃ for 60min, and natural cooling is performed to obtain a perovskite layer 3 with a thickness of 630-670nm;

[0100] Step (C), preparing a chlorobenzene dispersion of Spiro-OMeTAD: dissolving 520 mg of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) in 1 mL of acetonitrile, stirring for 3 min, then dissolving 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene, adding 28.8 μL of 4-tert-butylpyridine (TBP) and 17.5 μL of Li-TFSI acetonitrile solution to prepare a chlorobenzene dispersion of Spiro-OMeTAD; coating the perovskite layer 3 by a solution method at a coating speed of 4000 rpm, and drying naturally to obtain a hole transport layer 4 with a film thickness of 80 nm;

[0101] Step (D), preparing the counter electrode layer 5: evaporating gold on the hole transport layer 4 to obtain the counter electrode layer 5 with a film thickness of 110 nm.

[0102] Thus, a normal perovskite solar cell was obtained, which was recorded as C-3.

[0103] Example 4 (Variation of Annealing Conditions in Step (A-4))

[0104] according to Figure 1 The steps for preparing the inverted perovskite solar cell are as follows:

[0105] Step (A) comprises the following steps (A-1) to (A-4):

[0106] Step (A-1): Place a clean transparent conductive glass 1 on a deposition substrate, 40 to 50 cm from the evaporation source;

[0107] Step (A-2): placing stannous oxide as a source material in the evaporation boat area;

[0108] Step (A-3): Use a pump set to evacuate the environment to a vacuum of 8 × 10 -5 Below Pa, the evaporation rate is controlled to 0.2A / s, and the thickness of the prepared film is controlled to 5nm;

[0109] Step (A-4): 10 wt% tin tetrachloride solution is coated on the film layer on the above-treated transparent conductive glass by a solution method to prepare SnO 2 The coating speed was 3000 rpm, and after coating, it was annealed at 150 ° C for 60 min and cooled naturally. A total film thickness of 30 nm of SnO was obtained on the transparent conductive glass 1. 2 Electron transport layer 2;

[0110] Step (B), preparation of perovskite layer 3: coating FA with a concentration of 1.4 mol / L on the electron transport layer 2 of step (A) 0.95 Cs0.05 PbI 3 The coating condition is 5000 rpm, the coating time is 30 s, chlorobenzene is added as an anti-solvent at 15 s, annealing is performed at 110 ° C for 60 min, and natural cooling is performed to obtain a perovskite layer 3 with a thickness of 650-690 nm;

[0111] Step (C), preparing a chlorobenzene dispersion of Spiro-OMeTAD: dissolving 520 mg of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) in 1 mL of acetonitrile, stirring for 3 min, then dissolving 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene, adding 28.8 μL of 4-tert-butylpyridine (TBP) and 17.5 μL of Li-TFSI acetonitrile solution to prepare a chlorobenzene dispersion of Spiro-OMeTAD; coating the perovskite layer 3 by a solution method at a coating speed of 4000 rpm, and drying naturally to obtain a hole transport layer 4 with a film thickness of 80 nm;

[0112] Step (D), preparing the counter electrode layer 5: evaporating gold on the hole transport layer 4 to obtain the counter electrode layer 5 with a film thickness of 110 nm.

[0113] Thus, a normal perovskite solar cell was obtained, which was recorded as C-4.

[0114] Example 5 (Variation of Annealing Conditions in Step (A-4))

[0115] according to Figure 1 The steps for preparing the inverted perovskite solar cell are as follows:

[0116] Step (A) comprises the following steps (A-1) to (A-4):

[0117] Step (A-1): Place a clean transparent conductive glass 1 on a deposition substrate, 40 to 50 cm from the evaporation source;

[0118] Step (A-2): placing stannous oxide as a source material in the evaporation boat area;

[0119] Step (A-3): Use a pump set to evacuate the environment to a vacuum of 8 × 10 -5 Below Pa, the evaporation rate is controlled to 0.2A / s, and the thickness of the prepared film is controlled to 5nm;

[0120] Step (A-4): 10 wt% tin tetrachloride solution is coated on the film layer on the above-treated transparent conductive glass by a solution method to prepare SnO 2The coating speed was 3000 rpm, and after coating, it was annealed at 300 ° C for 60 min and cooled naturally. A total film thickness of 30 nm of SnO was obtained on the transparent conductive glass 1. 2 Electron transport layer 2;

[0121] Step (B), preparation of perovskite layer 3: coating FA with a concentration of 1.4 mol / L on the electron transport layer 2 of step (A) 0.95 Cs 0.05 PbI 3 The coating condition is 5000 rpm, the coating time is 30 s, chlorobenzene is added as an anti-solvent at 15 s, annealing is performed at 110 ° C for 60 min, and natural cooling is performed to obtain a perovskite layer 3 with a thickness of 650-690 nm;

[0122] Step (C), preparing a chlorobenzene dispersion of Spiro-OMeTAD: dissolving 520 mg of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) in 1 mL of acetonitrile, stirring for 3 min, then dissolving 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene, adding 28.8 μL of 4-tert-butylpyridine (TBP) and 17.5 μL of Li-TFSI acetonitrile solution to prepare a chlorobenzene dispersion of Spiro-OMeTAD; coating the perovskite layer 3 by a solution method at a coating speed of 4000 rpm, and drying naturally to obtain a hole transport layer 4 with a film thickness of 80 nm;

[0123] Step (D), preparing the counter electrode layer 5: evaporating gold on the hole transport layer 4 to obtain the counter electrode layer 5 with a film thickness of 110 nm.

[0124] Thus, a normal perovskite solar cell was obtained, which was recorded as C-5.

[0125] Example 6 (changing the tin source to elemental tin)

[0126] according to Figure 1 The steps for preparing the inverted perovskite solar cell are as follows:

[0127] Step (A) comprises the following steps (A-1) to (A-4):

[0128] Step (A-1): Place a clean transparent conductive glass 1 on a deposition substrate, 40 to 50 cm from the evaporation source;

[0129] Step (A-2): placing single substance tin as source material in the evaporation boat area;

[0130] Step (A-3): Use a pump set to evacuate the environment to a vacuum of 8 × 10-5 Below Pa, the evaporation rate is controlled to 0.2A / s, and the thickness of the prepared film is controlled to 5nm;

[0131] Step (A-4): 10 wt% tin tetrachloride solution is coated on the film layer on the above-treated transparent conductive glass by a solution method to prepare SnO 2 The coating speed is 3000rpm. After coating, the temperature is raised from 100℃ to 200℃ for 30min. After annealing at 200℃ for 30min, the film is cooled naturally. A total film thickness of 30nm of SnO is obtained on the transparent conductive glass 1. 2 Electron transport layer 2;

[0132] Step (B), preparation of perovskite layer 3: coating FA with a concentration of 1.4 mol / L on the electron transport layer 2 of step (A) 0.95 Cs 0.05 PbI 3 solution, the coating condition is 5000rpm, the coating time is 30s, chlorobenzene is added as anti-solvent at 15s, annealing is carried out at 110℃ for 60min, and natural cooling is carried out to obtain a perovskite layer 3 with a thickness of 580-620nm;

[0133] Step (C), preparing a chlorobenzene dispersion of Spiro-OMeTAD: dissolving 520 mg of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) in 1 mL of acetonitrile, stirring for 3 min, then dissolving 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene, adding 28.8 μL of 4-tert-butylpyridine (TBP) and 17.5 μL of Li-TFSI acetonitrile solution to prepare a chlorobenzene dispersion of Spiro-OMeTAD; coating the perovskite layer 3 by a solution method at a coating speed of 4000 rpm, and drying naturally to obtain a hole transport layer 4 with a film thickness of 80 nm;

[0134] Step (D), preparing the counter electrode layer 5: evaporating gold on the hole transport layer 4 to obtain the counter electrode layer 5 with a film thickness of 110 nm.

[0135] Thus, a normal perovskite solar cell was obtained, which was recorded as C-6.

[0136] Example 7 (Change the tin source to stannous chloride (SnCl 2 ))

[0137] according to Figure 1 The steps for preparing the inverted perovskite solar cell are as follows:

[0138] Step (A) comprises the following steps (A-1) to (A-4):

[0139] Step (A-1): Place a clean transparent conductive glass 1 on a deposition substrate, 40 to 50 cm from the evaporation source;

[0140] Step (A-2): placing stannous chloride as a source material in the evaporation boat area;

[0141] Step (A-3): Use a pump set to evacuate the environment to a vacuum of 8 × 10 -5 Below Pa, the evaporation rate is controlled to 0.2A / s, and the thickness of the prepared film is controlled to 5nm;

[0142] Step (A-4): 10 wt% tin tetrachloride solution is coated on the film layer on the above-treated transparent conductive glass by a solution method to prepare SnO 2 The coating speed is 3000rpm. After coating, the temperature is raised from 100℃ to 200℃ for 30min. After annealing at 200℃ for 30min, the film is cooled naturally. A total film thickness of 30nm of SnO is obtained on the transparent conductive glass 1. 2 Electron transport layer 2;

[0143] Step (B), preparation of perovskite layer 3: coating FA with a concentration of 1.4 mol / L on the electron transport layer 2 of step (A) 0.95 Cs 0.05 PbI 3 solution, the coating condition is 5000rpm, the coating time is 30s, chlorobenzene is added as anti-solvent at 15s, annealing is carried out at 110℃ for 60min, and natural cooling is carried out to obtain a perovskite layer 3 with a thickness of 580-620nm;

[0144] Step (C), preparing a chlorobenzene dispersion of Spiro-OMeTAD: dissolving 520 mg of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) in 1 mL of acetonitrile, stirring for 3 min, then dissolving 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene, adding 28.8 μL of 4-tert-butylpyridine (TBP) and 17.5 μL of Li-TFSI acetonitrile solution to prepare a chlorobenzene dispersion of Spiro-OMeTAD; coating the perovskite layer 3 by a solution method at a coating speed of 4000 rpm, and drying naturally to obtain a hole transport layer 4 with a film thickness of 80 nm;

[0145] Step (D), preparing the counter electrode layer 5: evaporating gold on the hole transport layer 4 to obtain the counter electrode layer 5 with a film thickness of 110 nm.

[0146] Thus, a normal perovskite solar cell was obtained, which was recorded as C-7.

[0147] Example 8 (Variation of Annealing Conditions in Step (A-4))

[0148] according to Figure 1 The steps for preparing the inverted perovskite solar cell are as follows:

[0149] Step (A) comprises the following steps (A-1) to (A-4):

[0150] Step (A-1): Place a clean transparent conductive glass 1 (FTO glass) on a deposition substrate, 40 to 50 cm from the evaporation source;

[0151] Step (A-2): placing stannous oxide as a source material in the evaporation boat area;

[0152] Step (A-3): Use a pump set to evacuate the environment to a vacuum of 8 × 10 -5 Below Pa, the evaporation rate is controlled to 0.2A / s, and the thickness of the prepared film is controlled to 5nm;

[0153] Step (A-4): 10 wt% tin tetrachloride solution is coated on the film layer on the above-treated transparent conductive glass by a solution method to prepare SnO 2 The coating speed was 3000 rpm. After coating, it was annealed at 200°C for 60 min (directly placed on a 200°C constant temperature hot plate and then kept warm for 60 min), and then cooled naturally. A total film thickness of 30 nm of SnO was obtained on the transparent conductive glass 1. 2 Electron transport layer 2;

[0154] Step (B), preparation of perovskite layer 3: coating FA with a concentration of 1.4 mol / L on the electron transport layer 2 of step (A) 0.95 Cs 0.05 PbI 3 The coating condition is 5000 rpm, the coating time is 30 s, chlorobenzene is added as an anti-solvent at 15 s, annealing is performed at 110 ° C for 60 min, and natural cooling is performed to obtain a perovskite layer 3 with a thickness of 610-650 nm;

[0155] Step (C), preparing a chlorobenzene dispersion of Spiro-OMeTAD: dissolving 520 mg of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) in 1 mL of acetonitrile, stirring for 3 min, then dissolving 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene, adding 28.8 μL of 4-tert-butylpyridine (TBP) and 17.5 μL of Li-TFSI acetonitrile solution to prepare a chlorobenzene dispersion of Spiro-OMeTAD; coating the perovskite layer 3 by a solution method at a coating speed of 4000 rpm, and drying naturally to obtain a hole transport layer 4 with a film thickness of 80 nm;

[0156] Step (D), preparing the counter electrode layer 5: evaporating gold on the hole transport layer 4 to obtain the counter electrode layer 5 with a film thickness of 110 nm.

[0157] Thus, a normal perovskite solar cell was obtained, which was recorded as C-8.

[0158] Example 9 (SnO+ scraping electronic layer)

[0159] according to Figure 1 The steps for preparing the inverted perovskite solar cell are as follows:

[0160] Step (A) comprises the following steps (A-1) to (A-4):

[0161] Step (A-1): Place a clean transparent conductive glass 1 (FTO glass) on a deposition substrate, 40 to 50 cm from the evaporation source;

[0162] Step (A-2): placing stannous oxide as a source material in the evaporation boat area;

[0163] Step (A-3): Use a pump set to evacuate the environment to a vacuum of 8 × 10 -5 Below Pa, the evaporation rate is controlled to 0.2A / s, and the thickness of the prepared film is controlled to 5nm;

[0164] Step (A-4): 3.75 wt% tin tetrachloride solution is applied on the film layer on the above-treated transparent conductive glass by a solution method to prepare SnO 2 Film layer, initial velocity 2.4cm / s, acceleration 0.03cm / s 2 After coating, the temperature was raised from 100°C to 200°C for 30 min, annealed at 200°C for 30 min, and then cooled naturally. A total film thickness of 30 nm of SnO was obtained on the transparent conductive glass 1. 2 Electron transport layer 2;

[0165] Step (B), preparation of perovskite layer 3: coating FA with a concentration of 1.4 mol / L on the electron transport layer 2 of step (A) 0.95 Cs 0.05 PbI 3 solution, the coating condition is 5000rpm, the coating time is 30s, chlorobenzene is added as anti-solvent at 15s, annealing is performed at 110°C for 60min, and natural cooling is performed to obtain a perovskite layer 3 with a thickness of 660-700nm;

[0166] Step (C), preparing a chlorobenzene dispersion of Spiro-OMeTAD: dissolving 520 mg of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) in 1 mL of acetonitrile, stirring for 3 min, then dissolving 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene, adding 28.8 μL of 4-tert-butylpyridine (TBP) and 17.5 μL of Li-TFSI acetonitrile solution to prepare a chlorobenzene dispersion of Spiro-OMeTAD; coating the perovskite layer 3 by a solution method at a coating speed of 4000 rpm, and drying naturally to obtain a hole transport layer 4 with a film thickness of 80 nm;

[0167] Step (D), preparing the counter electrode layer 5: evaporating gold on the hole transport layer 4 to obtain the counter electrode layer 5 with a film thickness of 110 nm.

[0168] Thus, a normal perovskite solar cell was obtained, which was recorded as C-9.

[0169] Example 10 (SnO+slit-coated electronic layer)

[0170] according to Figure 1 The steps for preparing the inverted perovskite solar cell are as follows:

[0171] Step (A) comprises the following steps (A-1) to (A-4):

[0172] Step (A-1): Place a clean transparent conductive glass 1 (FTO glass) on a deposition substrate, 40 to 50 cm from the evaporation source;

[0173] Step (A-2): placing stannous oxide as a source material in the evaporation boat area;

[0174] Step (A-3): Use a pump set to evacuate the environment to a vacuum of 8 × 10 -5 Below Pa, the evaporation rate is controlled to 0.2A / s, and the thickness of the prepared film is controlled to 5nm;

[0175] Step (A-4): 0.5 wt% tin tetrachloride solution is coated on the film layer on the above-treated transparent conductive glass by a solution method to prepare SnO 2 The coating speed was 5.0 mm / s, the injection speed was 3.0 μL / s, and after coating, it was transferred to a hot plate and heated from 100°C to 200°C for 30 min. After annealing at 200°C for 30 min, it was naturally cooled. A total film thickness of 30 nm of SnO was obtained on the transparent conductive glass 1. 2 Electron transport layer 2;

[0176] Step (B), preparation of perovskite layer 3: coating FA with a concentration of 1.4 mol / L on the electron transport layer 2 of step (A) 0.95 Cs 0.05 PbI 3 solution, the coating condition is 5000rpm, the coating time is 30s, chlorobenzene is added as anti-solvent at 15s, annealing is performed at 110°C for 60min, and natural cooling is performed to obtain a perovskite layer 3 with a thickness of 660-700nm;

[0177] Step (C), preparing a chlorobenzene dispersion of Spiro-OMeTAD: dissolving 520 mg of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) in 1 mL of acetonitrile, stirring for 3 min, then dissolving 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene, adding 28.8 μL of 4-tert-butylpyridine (TBP) and 17.5 μL of Li-TFSI acetonitrile solution to prepare a chlorobenzene dispersion of Spiro-OMeTAD; coating the perovskite layer 3 by a solution method at a coating speed of 4000 rpm, and drying naturally to obtain a hole transport layer 4 with a film thickness of 80 nm;

[0178] Step (D), preparing the counter electrode layer 5: evaporating gold on the hole transport layer 4 to obtain the counter electrode layer 5 with a film thickness of 110 nm.

[0179] Thus, a normal perovskite solar cell was obtained, which was recorded as C-10.

[0180] Example 11 (SnO+Sprayed Electronic Layer)

[0181] according to Figure 1 The steps for preparing the inverted perovskite solar cell are as follows:

[0182] Step (A) comprises the following steps (A-1) to (A-4):

[0183] Step (A-1): Place a clean transparent conductive glass 1 (FTO glass) on a deposition substrate, 40 to 50 cm from the evaporation source;

[0184] Step (A-2): placing stannous oxide as a source material in the evaporation boat area;

[0185] Step (A-3): Use a pump set to evacuate the environment to a vacuum of 8 × 10 -5 Below Pa, the evaporation rate is controlled to 0.2A / s, and the thickness of the prepared film is controlled to 5nm;

[0186] Step (A-4): Spraying a 1.0 wt% tin tetrachloride solution on the film layer on the above-treated transparent conductive glass by a solution method to prepare SnO 2 The spraying instrument was adjusted to make the gas flow rate 4L / min, the liquid flow rate 10mL / min, the step length 15cm, the spraying height about 50cm, and the spraying times 8 times. After spraying, the temperature was raised from 100℃ to 200℃ for 30min, annealed at 200℃ for 30min, and then cooled naturally; a total film thickness of 30nm of SnO was obtained on the transparent conductive glass 1. 2 Electron transport layer 2;

[0187] Step (B), preparation of perovskite layer 3: coating FA with a concentration of 1.4 mol / L on the electron transport layer 2 of step (A) 0.95 Cs 0.05 PbI 3 solution, the coating condition is 5000rpm, the coating time is 30s, chlorobenzene is added as anti-solvent at 15s, annealing is performed at 110°C for 60min, and natural cooling is performed to obtain a perovskite layer 3 with a thickness of 660-700nm;

[0188] Step (C), preparing a chlorobenzene dispersion of Spiro-OMeTAD: dissolving 520 mg of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) in 1 mL of acetonitrile, stirring for 3 min, then dissolving 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene, adding 28.8 μL of 4-tert-butylpyridine (TBP) and 17.5 μL of Li-TFSI acetonitrile solution to prepare a chlorobenzene dispersion of Spiro-OMeTAD; coating the perovskite layer 3 by a solution method at a coating speed of 4000 rpm, and drying naturally to obtain a hole transport layer 4 with a film thickness of 80 nm;

[0189] Step (D), preparing the counter electrode layer 5: evaporating gold on the hole transport layer 4 to obtain the counter electrode layer 5 with a film thickness of 110 nm.

[0190] Thus, a normal perovskite solar cell was obtained, which was recorded as C-11.

[0191] Comparative Example 1 (preparation of electron transport layer by thermal evaporation method only, film thickness 5 nm)

[0192] according to Figure 1 The steps for preparing the inverted perovskite solar cell are as follows:

[0193] Step (A) comprises the following steps (A-1) to (A-4):

[0194] Step (A-1): Place clean transparent conductive glass (FTO glass) on a deposition substrate, 40 to 50 cm from the evaporation source;

[0195] Step (A-2): placing stannous oxide as a source material in the evaporation boat area;

[0196] Step (A-3): Use a pump set to evacuate the environment to a vacuum of 8 × 10 -5 Below Pa, the evaporation rate is controlled to 0.2A / s, and the thickness of the prepared film is controlled to 5nm;

[0197] Step (A-4): placing the substrate obtained above in an air environment and heating it from 100° C. to 200° C. for 30 min, and annealing at 200° C. for 30 min;

[0198] Step (B), preparation of perovskite layer 3: coating FA with a concentration of 1.4 mol / L on the electron transport layer 2 of step (A) 0.95 Cs 0.05 PbI 3 solution, the coating condition is 5000rpm, the coating time is 30s, chlorobenzene is added as anti-solvent at 15s, annealing is carried out at 110℃ for 60min, and natural cooling is carried out to obtain a perovskite layer 3 with a thickness of 480-520nm;

[0199] Step (C), preparing a chlorobenzene dispersion of Spiro-OMeTAD: dissolving 520 mg of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) in 1 mL of acetonitrile, stirring for 3 min, then dissolving 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene, adding 28.8 μL of 4-tert-butylpyridine (TBP) and 17.5 μL of Li-TFSI acetonitrile solution to prepare a chlorobenzene dispersion of Spiro-OMeTAD; coating the perovskite layer 3 by a solution method at a coating speed of 4000 rpm, and drying naturally to obtain a hole transport layer 4 with a film thickness of 80 nm;

[0200] Step (D), preparing the counter electrode layer 5: evaporating gold on the hole transport layer 4 to obtain the counter electrode layer 5 with a film thickness of 110 nm.

[0201] Thus, a normal perovskite solar cell was obtained, which was recorded as C-12.

[0202] Comparative Example 2 (preparation of electron transport layer by thermal evaporation method only, film thickness 30 nm)

[0203] according to Figure 1 The steps for preparing the inverted perovskite solar cell are as follows:

[0204] Step (A) comprises the following steps (A-1) to (A-4):

[0205] Step (A-1): Place clean transparent conductive glass (FTO glass) on a deposition substrate, 40 to 50 cm from the evaporation source;

[0206] Step (A-2): placing stannous oxide as a source material in the evaporation boat area;

[0207] Step (A-3): Use a pump set to evacuate the environment to a vacuum of 8 × 10 -5 Below Pa, the evaporation rate is controlled at 0.2A / s, and the thickness of the prepared film is controlled at 30nm;

[0208] Step (A-4): placing the substrate obtained above in an air environment and heating it from 100° C. to 200° C. for 30 min, and annealing at 200° C. for 30 min;

[0209] Step (B), preparation of perovskite layer 3: coating FA with a concentration of 1.4 mol / L on the electron transport layer 2 of step (A) 0.95 Cs 0.05 PbI 3 solution, the coating condition is 5000rpm, the coating time is 30s, chlorobenzene is added as anti-solvent at 15s, annealing is carried out at 110℃ for 60min, and natural cooling is carried out to obtain a perovskite layer 3 with a thickness of 530-570nm;

[0210] Step (C), preparing a chlorobenzene dispersion of Spiro-OMeTAD: dissolving 520 mg of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) in 1 mL of acetonitrile, stirring for 3 min, then dissolving 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene, adding 28.8 μL of 4-tert-butylpyridine (TBP) and 17.5 μL of Li-TFSI acetonitrile solution to prepare a chlorobenzene dispersion of Spiro-OMeTAD; coating the perovskite layer 3 by a solution method at a coating speed of 4000 rpm, and drying naturally to obtain a hole transport layer 4 with a film thickness of 80 nm;

[0211] Step (D), preparing the counter electrode layer 5: evaporating gold on the hole transport layer 4 to obtain the counter electrode layer 5 with a film thickness of 110 nm.

[0212] Thus, a normal perovskite solar cell was obtained, which was recorded as C-13.

[0213] Comparative Example 3 (Preparation of Electron Transport Layer by Coating Method Only)

[0214] according to Figure 1 The steps for preparing the inverted perovskite solar cell are as follows:

[0215] Step (A): 10 wt% tin tetrachloride solution is coated on clean transparent conductive glass (FTO glass) by solution method to prepare SnO 2 The coating speed is 3000rpm. After coating, the temperature is raised from 100℃ to 200℃ for 30min. After annealing at 200℃ for 30min, the film is cooled naturally. A total film thickness of 25nm of SnO is obtained on the transparent conductive glass 1. 2 Electron transport layer 2;

[0216] Step (B), preparation of perovskite layer 3: coating FA with a concentration of 1.4 mol / L on the electron transport layer 2 of step (A) 0.95 Cs 0.05 PbI 3 The coating conditions were 5000 rpm, the coating time was 30 s, chlorobenzene was added as an anti-solvent at the 15th second, annealing was performed at 110° C. for 60 min, and natural cooling was performed to obtain a perovskite layer 3 with a thickness of 610 to 650 nm.

[0217] Step (C), preparing a chlorobenzene dispersion of Spiro-OMeTAD: dissolving 520 mg of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) in 1 mL of acetonitrile, stirring for 3 min, then dissolving 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene, adding 28.8 μL of 4-tert-butylpyridine (TBP) and 17.5 μL of Li-TFSI acetonitrile solution to prepare a chlorobenzene dispersion of Spiro-OMeTAD; coating the perovskite layer 3 by a solution method at a coating speed of 4000 rpm, and drying naturally to obtain a hole transport layer 4 with a film thickness of 80 nm;

[0218] Step (D), preparing the counter electrode layer 5: evaporating gold on the hole transport layer 4 to obtain the counter electrode layer 5 with a film thickness of 110 nm.

[0219] Thus, a normal perovskite solar cell was obtained, which was recorded as C-14.

[0220] Comparative Example 4 (Preparation of electron transport layer by thermal evaporation method + coating method, two annealings)

[0221] according to Figure 1 The steps for preparing the inverted perovskite solar cell are as follows:

[0222] Step (A) comprises the following steps (A-1) to (A-5):

[0223] Step (A-1): Place clean transparent conductive glass (FTO glass) on a deposition substrate, 40 to 50 cm from the evaporation source;

[0224] Step (A-2): placing stannous oxide as a source material in the evaporation boat area;

[0225] Step (A-3): Use a pump set to evacuate the environment to a vacuum of 8 × 10 -5 Below Pa, the evaporation rate is controlled to 0.2A / s, and the thickness of the prepared film is controlled to 5nm;

[0226] Step (A-4): annealing the substrate at 200° C. for 60 min;

[0227] Step (A-5): 10 wt% tin tetrachloride solution is coated on the film layer on the above-treated transparent conductive glass by a solution method to prepare SnO 2 The coating speed was 3000 rpm. After coating, the temperature was raised from 100°C to 200°C for 30 min. After annealing at 200°C for 30 min, the film was cooled naturally. A total film thickness of 30 nm of SnO was obtained on the FTO glass. 2Electron transport layer 2;

[0228] Step (B), preparation of perovskite layer 3: coating FA with a concentration of 1.4 mol / L on the electron transport layer 2 of step (A) 0.95 Cs 0.05 PbI 3 The coating condition is 5000 rpm, the coating time is 30 s, chlorobenzene is added as an anti-solvent at 15 s, annealing is performed at 110 ° C for 60 min, and natural cooling is performed to obtain a perovskite layer 3 with a thickness of 640-680 nm;

[0229] Step (C), preparing a chlorobenzene dispersion of Spiro-OMeTAD: dissolving 520 mg of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) in 1 mL of acetonitrile, stirring for 3 min, then dissolving 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene, adding 28.8 μL of 4-tert-butylpyridine (TBP) and 17.5 μL of Li-TFSI acetonitrile solution to prepare a chlorobenzene dispersion of Spiro-OMeTAD; coating the perovskite layer 3 by a solution method at a coating speed of 4000 rpm, and drying naturally to obtain a hole transport layer 4 with a film thickness of 80 nm;

[0230] Step (D), preparing the counter electrode layer 5: evaporating gold on the hole transport layer 4 to obtain the counter electrode layer 5 with a film thickness of 110 nm.

[0231] Thus, a normal perovskite solar cell was obtained, which was recorded as C-15.

[0232] Test Example 1

[0233] (1) The performance of the batteries prepared in the above examples and comparative examples was tested, and the results are shown in Table 1.

[0234] The performance of the upright perovskite solar cells C-1 to C-15 of Examples 1 to 11 and Comparative Examples 1 to 4 are shown in Table 1, wherein the aging condition is the photoelectric conversion efficiency retention rate after 1 sun illumination at room temperature.

[0235] Table 1

[0236]

[0237] (2) The IV efficiency of the batteries prepared in the examples and comparative examples was tested, wherein the IV efficiency test graphs of Example 1 and Comparative Examples 1 to 4 were as shown in FIG. Figure 2 shown.

[0238] According to Table 1 and Figure 2The data show that compared with the solar cell device with a thin electron layer substrate prepared by single-layer thermal evaporation (Comparative Example 1, C-12), the solar cell device with tin oxide as the electron transport layer prepared by single-layer thermal evaporation (Comparative Example 2, C-13), and the solar cell device with tin oxide electron layer substrate prepared by single-layer solution method (coating method) (Comparative Example 3, C-14), the device based on thermally evaporated thin layer of stannous oxide as the substrate and then assisted by tin tetrachloride to prepare the tin oxide electron layer (Example 1, C-1) has higher photoelectric conversion efficiency and stability; at the same time, the effect of the device obtained by annealing stannous oxide and tin tetrachloride precursors (twice annealing) in Comparative Example 4 (C-15) is weaker than the effect of stannous oxide assisting tin tetrachloride to convert tin oxide electron layer (only annealing once) in Example 1 (C-1). Therefore, from Figure 2 From Table 1, it can be concluded that the device prepared by in-situ growth of tin oxide electron transport layer with the assistance of tin tetrachloride after only one annealing with the tin oxide electron layer primed by thermal evaporation has better photoelectric conversion efficiency and stability.

[0239] Test Example 2

[0240] (1) The photoelectric conversion efficiency of the devices prepared in Example 1 and Comparative Examples 2 to 4 was tested, and the photoelectric conversion efficiency was normalized over time. The test results are shown in Figure 3 As shown (under unencapsulated conditions, the thin layer of tin oxide electronic layer prepared by thermal evaporation of a single layer in Comparative Example 1 cannot constitute effective charge transport and has extremely low efficiency, so no stability test was performed).

[0241] Figure 3 The light stability of the upright perovskite solar cells of Example 1 and Comparative Examples 2 to 4 is compared. The tin oxide electron layer prepared by single-layer thermal evaporation is adjusted to a normal electron layer thickness of 30nm. Comparative Example 2 (C-13) is treated with 1 sunlight for 250h at room temperature, and the photoelectric conversion efficiency decays to 9.8%; while Comparative Example 3 (C-14) decays to 12.3%; Comparative Example 4 (C-15) decays to 6.7%; The device (Example 1, C-1) based on the electron transport layer prepared by the method of the present invention shows excellent light stability, and the photoelectric conversion efficiency decays by only 2.2% after being treated with 1 sunlight for 250h at room temperature. The above results prove that the device with a tin oxide electron transport layer assisted by tin tetrachloride in situ growth of tin oxide electron transport layer with a stannous oxide electron layer based on thermal evaporation has higher light stability, and it has a significant effect of improving efficiency, which is conducive to the commercial application and promotion of perovskite solar cells.

[0242] (2) The electron transport layers prepared in step (A) of Comparative Example 2, Comparative Example 3 and Example 1 were analyzed by scanning electron microscopy. The results are shown in FIG. Figure 4At the same time, the compactness of the electron transport layer prepared in Comparative Example 3 and Example 1 was analyzed by an electrochemical test method. Specifically, Ag / AgCl was used as a reference electrode, and a cyclic voltammetry (CV) test was performed on the electron transport layer prepared in Example 1 and Comparative Example 3 by step (A). The results are shown in Figure 5 ; Among them, FTO / SnCl 4 The results of comparative example 3, FTO / SnO / SnCl 4 The results of Example 1 are as follows; after the electron transport layer film prepared in step (A) of Example 1, Comparative Example 2 and Comparative Example 3 was scraped to collect the powder, the obtained powder and the stannous oxide evaporation material powder were analyzed by X-ray diffraction, and the results are shown in FIG. Figure 6 ; Among them, SnO+SnCl 4 -H 2 O-200℃ for Example 1, SnCl 4 -H 2 The result of SnO-200℃ is comparative example 3, the result of SnO-200℃ is comparative example 2, and SnO is stannous oxide evaporation material powder.

[0243] Depend on Figure 4 It can be seen that SnO assists SnCl 4 Generate an electron transport layer and reduce holes. Figure 5 Electrochemical test shows that when the surface of FTO is covered with a layer of semiconductor tin oxide, the overall conductivity will decrease. The more uniform the coverage and the denser the film layer, the less leakage of the overall film layer, the smaller the curve cavity in the graph, and the lower the current density. Figure 5 It can be seen that the FTO / SnO / SnCl prepared in Example 1 4 The density of the film layer is significantly improved; Figure 6 It can be seen that SnO coordinates SnCl 4 The electron transport layer is generated and the crystallinity is improved; in summary, SnO is used to assist SnCl 4 Growth can obtain an electron transport layer with better density and higher quality.

[0244] In the description of the present application, it should be noted that the terms "upper", "lower", "inside", "outside", "front", "back", "left", "right", etc. indicate directions or positional relationships based on the directions or positional relationships in the working state of the present application. They are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, they should not be understood as limitations on the present application.

[0245] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "install", "connect" and "connect" should be understood in a broad sense. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0246] The present application has been described above in conjunction with preferred embodiments, but these embodiments are only exemplary and serve only as an illustration. On this basis, various replacements and improvements may be made to the present application, all of which fall within the scope of protection of the present application.

Claims

1. A method for preparing a SnO2 electron transport layer, characterized in that: The steps include: (1) thermally evaporating a tin source onto the conductive glass to form a film layer; wherein the tin source is selected from SnO, Sn or SnCl2; (2) A SnO2 precursor solution is coated on the film layer, and then air annealing is performed to form a SnO2 electron transport layer on the conductive glass.

2. The preparation method according to claim 1, characterized in that: In step (1), thermally evaporating the tin source onto the conductive glass to form a film layer comprises the following steps: (S1) placing the conductive glass on a deposition substrate, 40 to 50 cm away from an evaporation source; (S2) placing the tin source as the source material in the evaporation boat area, and evacuating the environment to 8×10 -5 Pa, the tin source is evaporated onto the conductive glass at a rate of 0.1-1 A / s to form a film layer.

3. The preparation method according to claim 1, characterized in that: The thickness of the film layer obtained in step (1) is 1 to 20 nm, preferably 1 to 15 nm.

4. The preparation method according to claim 1, characterized in that: The thickness of the SnO2 electron transport layer obtained in step (2) is 2 to 50 nm, preferably 20 to 40 nm.

5. The preparation method according to claim 1, characterized in that: The annealing in step (2) is carried out in an atmospheric environment at 150-500° C. for 0.25-12 h, preferably at 150-400° C. for 0.25-4 h, and more preferably firstly heating from 80-120° C. to 180-220° C. over 15-45 min, and then annealing at this temperature for 15-45 min.

6. The preparation method according to claim 1, characterized in that: The SnO2 precursor solution in step (2) is a solution of one or more components selected from tin tetrachloride, stannous chloride, sodium stannate, and Sn(N(CH3)2)4.

7. A SnO2 electron transport layer, characterized in that: The invention is prepared by the preparation method according to any one of the preceding claims.

8. A perovskite solar cell, characterized in that: The electron transport layer located on the conductive glass is the SnO2 electron transport layer described in claim 7.

9. The perovskite solar cell according to claim 8, characterized in that: It also includes a perovskite layer, a hole transport layer and a counter electrode layer located on the electron transport layer.

10. The perovskite solar cell according to claim 9, characterized in that: The thickness of the perovskite layer is 300-700 nm; The perovskite material in the perovskite layer is a semiconductor compound with an ABX3 structure; wherein A is one or more monovalent organic cations selected from amine, amidine, guanidine and cesium; B is one or more metal ions selected from lead, tin, rubidium, silver, bismuth, silicon and magnesium, and the molar percentage of lead ions in B is not less than 50%; X is one or more selected from iodide, chloride, bromide, thiocyanate and acetate; The thickness of the hole transport layer is 60 to 120 nm; The organic hole material in the hole transport layer is one or more selected from Spiro-OMeTAD, poly-TPD, copper phthalocyanine, nickel phthalocyanine, high molecular weight poly(triarylamine) and poly(3-hexylthiophene); The thickness of the counter electrode layer is 60 to 120 nm; The electrode material in the counter electrode layer is one or more selected from gold, silver, copper, nickel, tin, carbon and ITO.

Citation Information

Patent Citations

  • Method for preparing tin dioxide crystal by thermal evaporation

    CN109553126A

  • Composite electron transport layer and preparation method and application thereof

    CN115915871A